2017
DOI: 10.1182/blood-2017-03-772368
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of allogeneic hematopoietic cell transplantation in patients aged 70 years and older in the United States

Abstract: In this study, we evaluated trends and outcomes of allogeneic hematopoietic cell transplantation (HCT) in adults ≥70 years with hematologic malignancies across the United States. Adults ≥70 years with a hematologic malignancy undergoing first allogeneic HCT in the United States between 2000 and 2013 and reported to the Center for International Blood and Marrow Transplant Research were eligible. Transplant utilization and transplant outcomes, including overall survival (OS), progression-free survival (PFS), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(158 citation statements)
references
References 32 publications
9
146
0
3
Order By: Relevance
“…The retrospective nature of this analysis limits its interpretation, and prospective studies will important to validate the observations we have made and limit selection bias. It is important also to note that the age of the cohort treated with IC in this study is lower than the transplant cohort, although this may be of less relevance given the increasing age at which allogeneic transplants can now be delivered with relative safety . Future studies on larger patient cohorts with more detailed molecular analyses will provide important information concerning whether specific molecular abnormalities predict either relapse risk or its kinetics.…”
Section: Discussionmentioning
confidence: 95%
“…The retrospective nature of this analysis limits its interpretation, and prospective studies will important to validate the observations we have made and limit selection bias. It is important also to note that the age of the cohort treated with IC in this study is lower than the transplant cohort, although this may be of less relevance given the increasing age at which allogeneic transplants can now be delivered with relative safety . Future studies on larger patient cohorts with more detailed molecular analyses will provide important information concerning whether specific molecular abnormalities predict either relapse risk or its kinetics.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3]. On the basis of discoveries in a preclinical canine model of transplantation (4), a truly nonmyeloablative conditioning regimen consisting of 2 Gy total body irradiation (TBI) with or without added fludarabine has been developed by the Seattle team (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…showed an increased number of transplants for older patients, 16 including alternative donor transplants, 17 with outcomes similar to those of HLA-matched donors. 18 Multiple studies have demonstrated that AHCT can provide long-term survival benefit in elderly AML patients with high risk for disease relapse, and advanced age per se should not be used as a contraindication for AHCT.…”
Section: Blood and Marrow Transplant Research (Cibmtr)mentioning
confidence: 99%